The Turkish Mini Istanbul Qur'an by Mbah Hasan Pati: A Codicological Study of an Antique Printed Muṣḥaf - Alayya Ahsanu Nadiya; Ahmad Atabik; Aziizatul Khusniyah; Ravida Chauria Shavir (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2026)
This article examines the Turkish Istanbul Mini Qur'an preserved by Mbah Hasan Pati, an antique printed muṣḥaf circulating in the Indonesian archipelago, from a codicological perspective. While codicological studies have largely focused on handwritten Qur'anic manuscripts, antique printed muṣḥafs owned by private collectors remain understudied despite their historical significance. This study aims to identify the provenance of the muṣḥaf, describe its material and typographical features, and analyze its historical and religious significance within the transmission of printed Qur'ans in the Malay-Indonesian world. Employing qualitative field research with a descriptive-analytical approach, the study applies codicological analysis based on direct observation, interviews, and documentation. The findings indicate that the muṣḥaf is an authentic Turkish Istanbul printed Qur'an displaying the distinctive features of Ottoman miniature Qur'ans. Its presence in Indonesia reflects the transregional circulation of Ottoman printed Qur'ans and demonstrates the enduring historical, cultural, and religious value attributed to such artefacts by local Muslim communities. Although it is not a handwritten manuscript, this printed muṣḥaf constitutes an important codicological object that broadens the scope of Qur'anic codicology beyond manuscript culture to include early printed Qur'ans. The study underscores the importance of preserving antique printed muṣḥafs as part of the documentary heritage of the Qur'an in the Indonesian archipelago.